Caffeine intake interacts with Asian gene variants in Parkinson's disease: a study in 4488 subjectsResearch in context - Yi-Lin Ong; Xiao Deng; Hui-Hua Li; K. Narasimhalu; Ling-Ling Chan; Kumar M. Prakash; Wing-Lok Au; Pavanni Ratnagopal; Louis C.S. Tan; Eng-King Tan (Elsevier, 2023)
Summary: Background: Caffeine intake reduces risk of Parkinson's disease (PD), but the interaction with genes is unclear. The interaction of caffeine with genetic variants in those at high PD risk has healthcare importance. We investigate interactions of caffeine intake with risk variants found in Asians, and determine PD risk estimates in caffeine-drinkers carrying these variants. Methods: PD patients and controls without neurological disorders were included. Caffeine intake was assessed using a validated evaluation tool. Leucine rich repeat kinase 2 (LRRK2) risk variants were genotyped. Statistical analysis was conducted with logistic regression models. Gene-caffeine interactions were quantified using attributable proportion (AP) due to interaction (positive interaction defined as AP >0). Findings: 5100 subjects were screened and 4488 subjects (1790 PD, 2698 controls) with genetic data of at least one LRRK2 variant were included. Risk-variant-carriers who were non-caffeine-drinkers had increased PD odds compared to wildtype carriers who were caffeine-drinkers for G2385R [OR 8.6 (2.6-28.1) p < 0.001; AP = 0.71], R1628P [OR 4.6 (1.6-12.8) p = 0.004; AP = 0.50] and S1647T [OR 4.0 (2.0-8.1) p < 0.001; AP = 0.55] variants. Interpretation: Caffeine intake interacts with LRRK2 risk variants across three different groups of gene carriers. Asymptomatic risk-variant-carriers who are non-caffeine-drinkers have four to eight times greater PD risk compared to wildtype-caffeine-drinkers. Lifestyle modifications to mitigate PD risk in asymptomatic healthy risk variant carriers have potential roles in our Asian cohort. Funding: This study was supported by the National Medical Research Council (STaR and PD OF LCG 000207 grants) and Duke-NUS Medical School.